(3cJGH aj GdCOhjI GdeSgdI hGdYdGL HGdESgGds - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd efGaY GdYdGL HGdESgGd hGNJdGa GdCOhjI GdeSgdI ai LhgQgG hbhGgG hCaYGdgG GdHGH GdChd eG GdaQb Hjf GdGOhjI s
(3BNQgG (B:s
(3hgPG cGma ajeG PcQfGg ai Cbhi GdGOhjI GdeSgdI hGdYdGL HGdESgGd Je HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs